A HYPOTHETICAL COMBINATION METHOD TO PROVIDE DATA FOR FORMATION WATER COMPATIBILITY - Herlan Adim (Scientific Contributions Oil and Gas, 1999)
Industrial Water Technology, information concerning formation water, is required primarily in water injection projects to define the possibility of injection well plugging.